DNA sequence recognition by an imidazole-containing isopropyl-substituted thiazole polyamide (thiazotropsin B). - Hampshire, A; Khairallah, H; Khalaf, A; Ebrahimabadi, A; Waigh, R; Suckling, C; Brown, T; Fox, K (2006)
We have used DNA footprinting and fluorescence melting experiments to study the sequence specific binding of an imidazole-containing isopropyl-substituted thiazole polyamide (thiazotropsin B) to DNA. While the parent compound (thiazotropsin A) binds to the hexanucleotide sequence ACTAGT, changing one of the N-methylpyrrole groups to N-methylimidazole changes the preferred binding sequence to (A/T)CGCG(T/A). Experiments with DNA fragments that contain variants of this sequence suggest that the ligand can also bind, with lower affinity, to sequences which differ from this by 1bp in any position.